Health and lifestyle risk factors: a comparison between Brazilian athletes and non-athletes - Coelho-Ravagnani, Christianne de Faria (2025)
Introduction: Athletes are more exposed to mental and physical stress and injuries, affecting performance and health. However, evidence shows that endurance but not power athletes have greater longevity when compared to their non-athlete peers which could be explained by health factors. Objective: To compare the lifestyle characteristics and health profile between Brazilian athletes and non-athletes. Methods: This is a cross-sectional study comparing male athletes recruited between 2013 and 2016 (n = 147) representing 13 sports, which were divided into two categories: strength/velocity (SV) and endurance/mixed sports (EM). The non-athlete adult group was selected according to the National Health Survey. Athletes were assessed using health questionnaires, anthropometric, blood pressure and resting electrocardiograms measurements. Results: SV had higher body weight, body mass index, and blood pressure compared to the EM (p < 0.05). In addition, higher use of pharmacological substances, tobacco, and poor perception of health was observed in SV athletes. When compared to the non-athlete population, the EM showed a lower prevalence of overweight (56% vs. 26%), hypertension (18% vs. 3%), and self-reported depression (4% vs. 0%) while SV showed a higher prevalence of poor health perception (49% vs. 30%). Conclusions: Our findings reaffirm that athletes have higher health status than the general population but that more in-depth analysis must be carried out in sports with different natures.